Anticorpos presentes em amostras de líquido amniótico de pacientes com alto risco de toxoplasmose congênita reconhecem diferentes marcadores antigênicos de diferentes extratos proteicos de Toxoplasma gondii - Costa, Lucas Vasconcelos Soares (2019)
Toxoplasma gondii is an obligate intracellular parasite capable to infect a variety of hosts leading to toxoplasmosis. Generally, infected individuals are asymptomatic, but severe consequences for immunocompromised and pregnant women are described. Indeed, congenital toxoplasmosis occurs when tachyzoites pass throughout the placental barrier in pregnant women during the acute phase of infection leading to severe sequelae for the fetus and newborn if not properly treated. In cases of congenital transmission, it was possible to detect tachyzoites in amniotic fluid, a fluid that supports the growth of the embryo by reducing mechanical shocks and maintaining the temperature and pH. Considering the protection of antibodies presents in the amniotic fluid, the congenital infection can also occur in cases of reinfection with a different strain of the parasite. Thus, this study intended to investigate the behavior of maternal antibodies available in the amniotic fluid and its participation in fetal protection. Thirty-three amniotic fluid samples from patients at high risk of congenital toxoplasmosis, under treatment, were acquired by amniocentesis at the Hospital de Clínicas of the Universidade Federal de Uberlândia (HC-UFU). Clinical information about the pregnant women was obtained from their medical records. These samples were centrifuged, and the supernatant was used for detection of anti-T. gondii IgG levels by indirect ELISA. The results showed that only one patient was IgG negative in ELISA, and no difference was detected between IgG titles of chronic and acute phase of infection. To analyze the differences between electrophoretic profile among strains, soluble antigen extracts of T. gondii (STAg) from two clonal strains (RH and ME49) and three atypical strains (UDI-1, UDI-2 and Santa Maria) were separated by polyacrylamide gel 12% SDS-PAGE. The electrophoretic profile among the strains UDI-1, UDI-2, RH and ME49 was similar and a slightly difference in the Santa Maria’s isolate pattern was observed. The same extracts were also used to perform immunoblotting for determining the antigenic profile recognition of amniotic fluid samples against different strains. In addition, the immunoblotting-avidity assay was performed using samples with low IgG avidity reported in the medical records. It was demonstrated a distinct pattern of recognition by each strain. UDI-1 presented nine reactive fractions, being the one with the highest number of reactive bands. In avidity assay, antibodies exhibited moderate to high avidity against antigens from the RH, ME49, UDI-1 and Santa Maria strains. Two samples of amniotic fluid presented low avidity against UDI-2. Overall, our results showed a different antibody recognition profile against different strains of T. gondii, suggesting that antibodies produced during the first infection do not necessarily protect against reinfection by different strains. Additional studies will be necessary to understand how these T. gondii genotypes may interfere in the antibody production. And whether this distinct humoral response induced could be protective or not.